Landasan Pembangunan Industri Di Indonesia Studi Kasus PT Kimia Farma - Arsya Maharani Julia Putri; Hana Aulia Maysani; Indah Fitriana; Maryana Salma; Salsabila Nur Fadhilah; Naerul Edwin Kiky Aprianto (Journal Economic Excellence Ibnu Sina, 2024)
Indonesia needs an industrial structure that can grow sustainably, has high local potential, is resistant to global economic turmoil, and has a strong and synergistic relationship with other economic sectors and industrial subsectors. As a base for job creation, a producer of added value to regulate the domestic market, a generator of tax revenue and foreign exchange, and a driver of sustainable growth, the industrial sector plays an important role in the Indonesian economy. To achieve this, support from the government is needed through the provision of legal facilities in the form of a policy foundation that can encourage the creation of quality industrial development. the legal basis can be a reference and benchmark for industry players to be able to carry out their industrial processes and activities in line with national goals. Because the industrial sector is one of the important sectors in supporting the national economy. For this reason, it is necessary to have synergy between the government as a facility provider in the form of rules or policy bases that regulate industrial activities, and industry players as executors of policies issued by the government so that harmony can be created that can support sustainable industrial development in Indonesia.